Perancangan Sistem Kontrol Berbasis Arduino Uno pada Dispenser Penyedia Minuman Otomatis - Erham, Eddy (ReTII, 2019)
The accelerated development of digital electronic technology, make many people hope that can develop various facilities of a device. This condition become challenge for researchers. In this paper was developed some facilities of dispenser by designing its control system. The design includes of control system for temperature of drinking water, for the water level in a container and for pouring the water automatically. To do this, it was used electronic components, an Arduino Uno as a controller and some sensors as detectors and feedbacks. The Arduino was uploaded a control system program so that can function as controller. Whereas, for display, that work as monitor, was used Laptop which is supported PLX-DAQ and Ms. Excel. The results showed that control system responses have satisfied desired objectives. First, water temperature can be maintained at 80C , though still have error in range from 00C to 0.380C. Second, pouring the water as high as 5 cm can be performed automatically, with error in range from 0.2 cm to 0.5 cm. And finally, the container of water can provide the water without having any empty or overflow condition. Key words: Dispenser, Arduino, control system, pouring automatically, level control.